2017
DOI: 10.1371/journal.pone.0169999
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Novel c.820C>T (Arg274Trp) Mutation in the Mitofusin 2 Gene on Fibroblast Metabolism and Clinical Manifestation in a Patient

Abstract: Charcot-Marie-Tooth disease type 2A (CMT2A) is an autosomal dominant axonal peripheral neuropathy caused by mutations in the mitofusin 2 gene (MFN2). Mitofusin 2 is a GTPase protein present in the outer mitochondrial membrane and responsible for regulation of mitochondrial network architecture via the fusion of mitochondria. As that fusion process is known to be strongly dependent on the GTPase activity of mitofusin 2, it is postulated that the MFN2 mutation within the GTPase domain may lead to impaired GTPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Mitochondrial fission begins with the induction of Drp1. Mitochondrial fusion is a complex physiological process that involves optic atrophy 1 in the outer membrane and Mfn2 in the inner membrane [29] and depends on the MMP and hydrolysis of guanosine-5′-triphosphate [30]. e present investigation demonstrated reduced cardiac mitochondrial function in septic Nrf2 − /− mice as compared with that in their WT counterparts.…”
Section: Discussionsupporting
confidence: 49%
“…Mitochondrial fission begins with the induction of Drp1. Mitochondrial fusion is a complex physiological process that involves optic atrophy 1 in the outer membrane and Mfn2 in the inner membrane [29] and depends on the MMP and hydrolysis of guanosine-5′-triphosphate [30]. e present investigation demonstrated reduced cardiac mitochondrial function in septic Nrf2 − /− mice as compared with that in their WT counterparts.…”
Section: Discussionsupporting
confidence: 49%
“…Membrane fusion is a GTP-dependent process that depends on mitofusin 2 GTPase activity and consists of the following sequence of events: (i) binding of GTP to the GTPase domain leading to conformational changes of the GTP binding site; (ii) dimerization of two adjacent MFN2 molecules, which facilitates membrane proximity and their tethering and (iii) GTP-dependent outer membrane fusion associated with proper closure of mitofusin 2 10 . Several studies have demonstrated that MFN2 mutations affecting its GTPase domain (95–339 aa) alter mitochondria fusion, leading to changes in the mitochondrial shape from tubular to more oval 9 , 11 . Moreover, in mitofusin 2-mutant cells, mitochondria seem to extensively aggregate around nucleus and are nonfunctional for fusion 9 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in mitofusin 2-mutant cells, mitochondria seem to extensively aggregate around nucleus and are nonfunctional for fusion 9 , 12 . Mitochondrial network dysfunctions were also accompanied by reticular stress, diminished respiratory capacity and changes in mtDNA in patient–derived fibroblasts 11 13 . Another report suggested that mitochondrial network dysfunction is associated with impaired GTPase activity 9 while we have recently reported that p.Arg274Trp mutation does not influence GTP binding or GTPase activity 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations